PERFORMANCE OF JUNGLER’S CHAMPIONS IN THE GAME LEGUE OF LEGENDS - SILVA, Victor Ferreira; SILVA, Édipo Menezes; LIMA, Kelly Pereira; SCALON, João Domingos (Brazilian Journal of Biometrics, 2021)
Since the 1980s, there has been a widespread of high-speed internet connections, which is causing an expansion of the multiplayer electronic games industry. These games have gained the status of sport (called e-sports). Among these games, Lol (League of Legends R ) deserves special mention. In this game, players form a team of veand assume the role of a "champion" (characters with unique abilities) generally varying around a type of class, and battle against a team of player (or computer-controlled champions). A recurring problem is to balance these champions, that is, to leave the game as honest as possible, so that only the player’s ability will be a decisive factor for the victory. The aim of this work is to perform statistical analysis of the win rates of four champions of the tenth season of the Lol game mode "Wild Rift", doing control of the pachs. Using ANOVA and Tukey’s HSD test, we showed that even when we take only the champions with the highest winning rates, one of them stands out from the others.